2015
DOI: 10.1007/s12103-015-9299-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Police Among Hispanic Immigrants of Mexican Origin in the Southeast United States

Abstract: Studies have repeatedly shown that members of minority groups are likely to hold less favorable perceptions of the police than their white counterparts. Relying on a unique sample of nearly 70 Hispanic immigrants, this study expands current knowledge on correlates of Hispanics' perceptions of police. Overall, findings of this study indicate Hispanic immigrants of Mexican descent generally hold favorable views of the police. Results also suggest, however, that those who came to the US through illegal channels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…On the contrary, some studies have indicated a null or opposite relationship between language proficiency and perceptions toward the police. For instance, research conducted by Chu and Song (2015), Correia (2010), Khondaker et al (2017) and Roles et al (2016) has shown that language proficiency did not determine positive perceptions toward the police or was even associated with negative perceptions. Khondaker et al (2017) found that Bangladeshi immigrants in New York City were more likely to report illegal activities and communicate with the police when they were fearful of crime and satisfied with police, regardless of their English proficiency.…”
Section: English Proficiency and Cooperation With Police Among Immigr...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, some studies have indicated a null or opposite relationship between language proficiency and perceptions toward the police. For instance, research conducted by Chu and Song (2015), Correia (2010), Khondaker et al (2017) and Roles et al (2016) has shown that language proficiency did not determine positive perceptions toward the police or was even associated with negative perceptions. Khondaker et al (2017) found that Bangladeshi immigrants in New York City were more likely to report illegal activities and communicate with the police when they were fearful of crime and satisfied with police, regardless of their English proficiency.…”
Section: English Proficiency and Cooperation With Police Among Immigr...mentioning
confidence: 99%
“…For instance, research conducted by Chu and Song (2015), Correia (2010), Khondaker et al. (2017) and Roles et al. (2016) has shown that language proficiency did not determine positive perceptions toward the police or was even associated with negative perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit limited, the literature on immigrant perceptions of the police in the USA has been growing, with a number of immigrant groups, such as Latino, Bangladeshi, Vietnamese, Chinese, Korean, and Arab empirically examined (Cheurprakobkit, 2000; Cheurprakobkit and Bartsch, 1999; Chu and Hung, 2010; Chu and Song, 2015; Chu et al, 2005; Correia, 2010; Culver, 2004; Davis and Henderson, 2003; Davis and Hendricks, 2007; Herbst and Walker, 2001; Khondaker et al, 2015, 2017; Kirk et al, 2012; Menjivar, and Bejarano, 2004; Pogrebin and Poole, 1990; Roles et al, 2016; Skogan et al, 2002; Song, 1992; Sun and Wu, 2015; Torres and Vogel, 2001; Vidales et al, 2009; Walker, 1997; Wu, 2010; Wu et al, 2011, 2013). Other studies on Latino/Asian Americans were likely to include Latino/Asian immigrants in the samples, but they cannot claim with certainty that the results would apply to immigrant populations.…”
Section: Theorizing Immigrant Perception Of Policementioning
confidence: 99%
“…Yet in the few studies that have considered legal status, it plays an important role. For example, Mexican immigrants generally hold favorable views of the police, unless they came to the United States without inspection (Roles et al, 2016). We build on this scholarship by examining legal and citizenship status to demonstrate how Latinos as a group are racialized as undocumented in the context of immigration enforcement today.…”
Section: Immigrants' Views Of the Police And Crime Reportingmentioning
confidence: 99%